Study on Pressure Volume Temperature Relationship for Diatomic Solids Based On Inverted and Non Inverted Equations of State: Investigating the Pressure-Volume-Temperature Relationship for Diatomic Solids Using Inverted and Non-Inverted Equations of State (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The pressure-volume-temperature (P-V-T) relationship utilizing inverted and non-inverted conditions of state (EOS) for diatomic solids, for example, NaCl, MgO and LiH has been contemplated. It is tracked down that the inverted kind EOS because of yields close concurrence with the outcomes got from the non-inverted conditions due to for isothermal compressions just as isothermal mass modulus. The Roy - Roy inverted EOS has been found to have an extra benefit of foreseeing volumes for a strong at the same time raised pressure and temperature. We have utilized this EOS to get P-V-T results for NaCl and Mgo. The determined qualities present close concurrence with the exploratory data.